(untitled) (Journal of the College of Basic Education, 2022)
The present study investigate the effect of the effluents disposed from Al-Taji gas filling company on the water quality of river Tigris and its biotic composition, three stations were choosed, two of them represented river Tigris pre and post the pumping station of the company, while the other was within the company( Decanters).The following physicochemical parameters were measured: water temperature, current velocity, pH, EC, TDS, TSS, DO, BOD, COD, SO4-2 and Cl-1 , as well as the inspection of the major taxonomic groups of planktonic and benthic invertebrates. The results revealed that there is an increase in concentrations of the most studied parameters in the southern station of the river as compared with the northern one especially TDS, TSS, BOD, COD and SO4-2 and Cl-1. The faunal composition was varied in its distribution among the studied stations, the details were declared in the text.